An electrochemiluminescence aptasensor for analysis of bisphenol A based on carbon nanodots composite as co-reaction of Ru(bpy)32+ nanosheets. (1st October 2019) - Liu, Xiaohong; Luo, Lijun; Li, Libo; Di, Zhanxuan; Zhang, Jiayi; You, Tianyan
Abstract: An electrochemiluminescence (ECL) aptasensor based on poly(ethylenimine) functionalized nitrogen-doped carbon nanodots (NCDs@PEI) composite as co-reactant, and Ru(bpy)3 2+ nanosheets (RuNSs) as luminophor was constructed for the specific analysis of bisphenol A (BPA). On account of the double improvement functions of NCDs and PEI on RuNSs, the as-developed aptasensor exhibited superior ECL properties. In order to further enhance the selectivity of the RuNSs-NCDs@PEI system for BPA detection, we innovatively introduced the BPA aptamer to construct a novel ECL aptasensor. Compared with that without aptamer and with random DNA, the constructed aptasensor performed higher specificity for BPA determination under the interference of structural analogues. The as-prepared ECL aptasensor exhibited a wide linear range of 1.0 × 10 −10 - 1.0 × 10 −4  mol L −1, and a relatively low detection limit of 3.3 × 10 −11  mol L −1 for BPA detection with good stability and repeatability. Finally, when the ECL aptasensor made use of BPA analysis in water samples, the obtained results were confirmed by high performance liquid chromatography-ultraviolet spectrum (HPLC-UV) method, verifying its good accuracy. The novel aptasensor provided a new sensing platform for BPA in water samples.